2016
DOI: 10.1176/appi.ajp.2015.15070851
|View full text |Cite
|
Sign up to set email alerts
|

Dignity Therapy for Alcohol Use Disorder

Abstract: TO THE EDITOR: Dignity therapy is a short-term psychotherapeutic intervention shown to alleviate distress for people with life-limiting illnesses (1). In this therapy, patients generate a document to pass on to loved ones containing details of the patient's life, life lessons, and declarations of affection. Clinicians help create such documents by recording the patient's story and then transcribing and editing the patient's words. We report the case of a 46-year-old man with severe alcohol use disorder who att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The other nine articles were a mix of quantitative and qualitative analyses and case reports that included some consideration of the family member or caregiver of the patient receiving DT in their measurement, analysis, or discussion of DT, but these articles did not include direct measurement of any effect on the family member or caregiver (Table 2). 1422 Five of these nine articles represent studies in which patients receiving DT responded to some variant of the question if DT would “help” their family members or caregivers. Findings from these articles suggest that patients who receive DT feel it will be helpful to family members.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other nine articles were a mix of quantitative and qualitative analyses and case reports that included some consideration of the family member or caregiver of the patient receiving DT in their measurement, analysis, or discussion of DT, but these articles did not include direct measurement of any effect on the family member or caregiver (Table 2). 1422 Five of these nine articles represent studies in which patients receiving DT responded to some variant of the question if DT would “help” their family members or caregivers. Findings from these articles suggest that patients who receive DT feel it will be helpful to family members.…”
Section: Resultsmentioning
confidence: 99%
“…Two case reports of non-terminally-ill recipients of DT included findings that the therapy bettered communication or closeness between the patient and family members. 21,22 These 9 articles are included to reflect the full current state of the science of DT and family members; however, this literature review is primarily focused on the direct effects of DT on the family. An earlier review of the patient-focus of these studies (excluding Lubarsky, 2016, because it was not yet published) has been published.…”
Section: Resultsmentioning
confidence: 99%
“…A case study of a man with a history of generalised anxiety disorder and alcoholism revealed that DT “changed the story” of his life and resulted in a closer relationship with his family members, which helped support his sobriety (Lubarsky & Avery, ). Addiction research has found that recovering individuals benefit from the construction of narratives to help repair a person's sense of self, make sense of past drug use, and develop future non‐addict identities (Larkin & Griffiths, ; Singer, Singer, & Berry, ), which suggests that DT may help people with substance abuse issues, however, the authors suggest that future work is needed to adapt DT for this context.…”
Section: Resultsmentioning
confidence: 99%
“…Some interesting, although initial evidence has been published about the use of DT beyond terminal illnesses, namely for people with mental disorders such as depressive and alcohol use disorders, loss of meaning and hopelessness. [9][10][11][12] The preliminary results of these studies are promising and indicate that DT can be of clinical use beyond the field of end of life care.…”
Section: Dear Editormentioning
confidence: 92%